FOREIGN EXPERIENCE OF STATE REGULATING IN THE FIELD OF ENVIRONMENTAL PROTECTION - Bokovykova Yu.V.; Panova O.V. (Pressing Problems of Public Administration, 2018)
The experience of developed countries in the  eld of state regulation in the  eld of environmentalprotection has been analyzed. Effective modern regulatory instruments in the  eld of environmentalprotection have been dedicated. The conditions under which the use of foreign experience in Ukraineis possible have been determined.